2021
DOI: 10.3389/fgene.2021.772958
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Synonymous Mutation in NF1 Located at the Non-canonical Splicing Site Leading to Exon 45 Skipping

Abstract: Synonymous mutations are generally considered non-pathogenic because it did not alter the amino acids of the encoded protein. Publications of the associations between synonymous mutations and abnormal splicing have increased recently, however, not much observations available described the synonymous mutations at the non-canonical splicing sites leading to abnormal splicing. In this pedigree, the proband was diagnosed Neurofibromatosis type I due to the presence of typical cafe’ au lait macules and pectus carin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…EMC1 is a core subunit for the assembly and function of the EMC complex. Mutations in EMC1 have been associated with GDD in several studies (Harel et al, 2016;Geetha et al, 2018;Gao et al, 2019;Sun et al, 2019;Jin et al, 2021;Dhindsa et al, 2022) (Figure 2), where the affected individuals showed variable clinical presentation with major findings such as global developmental delay, cerebellar atrophy, psychomotor retardation, hypotonia, and visual impairment (Supplementary Table 1). The clinical features of the proband in current report are highly similar to the phenotypes described in previous individuals, supporting a diagnosis of EMC1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMC1 is a core subunit for the assembly and function of the EMC complex. Mutations in EMC1 have been associated with GDD in several studies (Harel et al, 2016;Geetha et al, 2018;Gao et al, 2019;Sun et al, 2019;Jin et al, 2021;Dhindsa et al, 2022) (Figure 2), where the affected individuals showed variable clinical presentation with major findings such as global developmental delay, cerebellar atrophy, psychomotor retardation, hypotonia, and visual impairment (Supplementary Table 1). The clinical features of the proband in current report are highly similar to the phenotypes described in previous individuals, supporting a diagnosis of EMC1-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of EMC1 is related to retinal degeneration, neural crest development defect, and glial abnormality in experimental animal models (Cabet et al, 2020;Chung et al, 2022;Dhindsa et al, 2022). To date, about a dozen of EMC1 variants, including missense, splice site, nonsense, and frameshift variants have been identified and associated with highly variable clinical presentation, ranging from isolated retinitis pigmentosa or congenital heart disease to severe global development delay (Harel et al, 2016;Geetha et al, 2018;Gao et al, 2019;Jin et al, 2021;Dhindsa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, as an absolute quantitative method with greater precision and sensitivity, ddPCR could be a promising technique for detection of mosaicism, especially for asymptomatic carriers who suffer from recurrent occurrence (Jin et al, 2021). Jin et al (2020) reported a case of tuberous sclerosis (TSC) with atypical clinical symptoms. They found a mosaic candidate mutation (c.1096G>T) by WES.…”
Section: Discussionmentioning
confidence: 99%
“…Synonymous mutations are often considered non-pathogenic because they do not alter the amino acid of the encoded protein; however, synonymous mutations at non-canonical splicing sites can lead to abnormal splicing, and reports about the relationship between synonymous mutations and abnormal splicing have increased recently ( 40 ). In our study, we found that the child has the synonymous variance c.3453C>T (p.Gly1151=) from the mother, and the location is near the splicing site at the 5’ end of the intron starts with the GT called donor, and the mutation creates a new donor site.…”
Section: Discussionmentioning
confidence: 99%